Meralgia Paresthetica Secondary to Adnexa Cyst: A Case Report - Maryam Behroozinia; Elham Sharifian; Saeid Khosrawi (Clinical Case Reports)
ABSTRACT Meralgia paresthetica (MP) is an entrapment syndrome of the lateral femoral cutaneous nerve characterized by tingling, numbness, itching and burning pain, and dysesthesia in anterolateral aspect of thigh. In this case report, we present a 37‐year‐old non‐obese female with 2‐month history of progressive pain and tingling on the anterolateral side of right thigh. Clinical features of patient were consistent with MP, which was confirmed via electrodiagnostic study. Subsequent abdominopelvic and transvaginal sonography revealed a mass‐like lesion measuring 92 × 61 mm in right adnexa adjacent to the right ovary. Following diagnosis, the patient underwent cystectomy, resulting in immediate resolution of symptoms. This case highlights the importance of comprehensive evaluation in patients presenting with MP symptoms, including consideration of abdominopelvic pathology as a potential contributing factor.